Ethnomedicinal uses of the Flora of Kohimoor Baba valley, Tribal District Bajaur, Khyber Pakhtunkhwa, Pakistan - Jan, Subhani; Jan, Gul; Irfan, Muhammad; Jan, Farzana Gul; Ullah, Fazal; Saeed, Muhammad (Ethnobotany Research and Applications, 2024)
Background: The present ethnomedicinal study was conducted in Kohimoor Baba valley, tribal district Bajaur, Khyber Pakhtunkhwa, Pakistan. The aims of the study were to document the medicinal plant resources and their usage patterns. Methods: To obtain the profile of flora and general information from the local people of the area. The specimens were collected in each visit from the protected vegetation sites. A total of 157 informants including (2 females and 155 males) were interviewed for data collection. The informants recognized 153 plant species in treatment of 71 different diseases. Most of them were aged between 30-70 years. The ethnobotanical data was collected through interviews among the local communities. Documented data was assessed using Informant Consensus Factor (ICF), Use Value (UV) and Fidelity Level (FL), Frequency citation (FC), and Relative Frequency of Citation (RFC). Results: A total of 153 taxa of plants belonged to 64 families were reported as being locally used for medicinal purposes. In collected specimens the 150 species belonged to Angiosperms while the Gymnosperms had one family with two species. However, the Pteridophytes had two families and each family had one species. Amongst the Angiosperms Lamiaceae was the dominant family with 12 species, followed by Asteraceae with 9 species, Fabaceae and Rosaceae with 8 species each. Based on habit wise distribution 91 (59.4%) species were herbs, while 33 (21.56%) were shrubs and 29 (18.95%) were trees. Leaves were the most commonly used plant parts of 69(45.09%) plants, followed by fruits 18 (14%), whole plants 16 (11.76%), roots 15 (9.80%), seeds 8 (5.22%), and bulb 6 (3.92%), latex and gums of 3 (1.96%), rhizome, flower and bark of 2 each (1.30%), while the rest of parts were used in a minor percent. The percentage of taxa used against digestive disorders was (28.57%), respiratory problems (15.58%), nail, skin and hairs diseases (11.68%), muscles and skeletal disorders (9.74%), nervous disorders (7.79%), anodyne (7.79%), body tonicity (6.49%), infectious diseases (4.54%) and (7.14%) for ear, nose and eye diseases. The highest value of informant consensus (0.8) was recorded for heart problems followed by sexual disorders (0.7). There were Prunus armeniaca (0.77), Salix babylonica (0.76), Dodonaea viscosa and Ficus carica (0.75), Vitex negundo (0.71), Berberis lycium (0.68), Podophyllum hexandrum had the top Fidelity level. Conclusion : The study was carried out for the first time in the area, which indicated that tribal district Bajaur has abundance of indigenous medicinal plants to cure a broad spectrum of human ailments. It was concluded that extinction and declines in plant diversity is due to a range of factor including heavy biotic interference, anthropogenic activity of humans, deforestation and overgrazing. It is recommended to create awareness in local communities about the conservation of these valuable medicinal plants. Keywords: Ethnobotany, Quantitative assessment, Kohimoor Baba valley, Pakistan.